2013
DOI: 10.1016/j.adt.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the astatine, radon, francium, and radium isotopes

Abstract: Currently, thirty-nine astatine, thirty-nine radon, thirty-five francium, and thirty-four radium isotopes have so far been observed; the discovery of these isotopes is discussed. For each isotope a brief summary of the first refereed publication, including the production and identification method, is presented. Contents IntroductionThe discovery of astatine, radon, francium, and radium isotopes is discussed as part of the series summarizing the discovery of isotopes, beginning with the cerium isotopes in 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 110 publications
(122 reference statements)
0
10
0
Order By: Relevance
“…20 The second reassignment involves 12 Li which was initially assigned to Yu. Aksyutina et al 21 In this work, 12 Li was populated in the reaction 1 H( 14 Be,2pn) 12 Li simultaneously with the discovery of 13 Li which was produced in the one-proton knockout reaction. However, it was recently pointed out 22 that the 12 Li data could have been contaminated by misidentified low energy two-neutron decay events from 13 Li invalidating the extracted scattering length for 12 Li.…”
Section: Changes Of Prior Assignmentsmentioning
confidence: 83%
See 1 more Smart Citation
“…20 The second reassignment involves 12 Li which was initially assigned to Yu. Aksyutina et al 21 In this work, 12 Li was populated in the reaction 1 H( 14 Be,2pn) 12 Li simultaneously with the discovery of 13 Li which was produced in the one-proton knockout reaction. However, it was recently pointed out 22 that the 12 Li data could have been contaminated by misidentified low energy two-neutron decay events from 13 Li invalidating the extracted scattering length for 12 Li.…”
Section: Changes Of Prior Assignmentsmentioning
confidence: 83%
“…Aksyutina et al 21 In this work, 12 Li was populated in the reaction 1 H( 14 Be,2pn) 12 Li simultaneously with the discovery of 13 Li which was produced in the one-proton knockout reaction. However, it was recently pointed out 22 that the 12 Li data could have been contaminated by misidentified low energy two-neutron decay events from 13 Li invalidating the extracted scattering length for 12 Li. This interpretation is also supported by the analysis of two-neutron events from the decay of 26 O which was performed with the same setup as the 12 Li experiment.…”
Section: Changes Of Prior Assignmentsmentioning
confidence: 83%
“…This element was discovered in 1940 by Corson et al [2] by bombarding a bismuth target with α particles. As described by Fry and Thoennessen [3] , thirty-nine astatine isotopes with atomic masses ranging from A = 191 to A = 229 have been discovered so far and, according to the Hartree-Fock-Bogoliubov (HFB-14) mass model [4] , about 37 additional astatine isotopes could exist. All of these isotopes are characterized by very short half-lives, the most stable species being 210 At with a half-life time of only 8.1 h. This isotope's primary decay mode is positron emission to the relatively long-lived and very toxic 210 Po.…”
Section: Introductionmentioning
confidence: 98%
“…Fry and Thoennessen [ 4 ] reported that thirty–nine isotopes of Astatine (At) have been discovered based on the Hartree-Fock-Bogoliubov model (HFB-14). Meanwhile, the discovery of 217 At was reported in 1947 by Hagemann et al, [ 5 ] and English et al, [ 6 ], by studying the decay series (4n+1) of 233 U.…”
Section: Introductionmentioning
confidence: 99%